2020
DOI: 10.18502/ijm.v12i5.4597
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of remdesivir in coronavirus disease 2019 (COVID-19): a systematic review

Abstract: Background and Objectives: Researchers all around the world are working hard to find an effective treatment for the new coronavirus 2019. We performed a comprehensive systematic review to investigate the latest clinical evidence on the efficacy and safety of treatment with Remdesivir in hospitalized patients with COVID-19. Materials and Methods: We performed a systematic search in Pubmed, Embase, Web of Science, Google scholar and MedRxiv for relevant observational and interventional studies. The outcomes meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…We included 36 reviews of remdesivir [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] plus two major living reviews of all treatments for COVID-19 [ 25 , 26 ] (collectively reported in 45 publications up to May 20, 2021). The first review was published on April 30, 2020 [42] , the day after the first randomized trial of remdesivir and the preliminary findings of two other trials were published.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 36 reviews of remdesivir [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] plus two major living reviews of all treatments for COVID-19 [ 25 , 26 ] (collectively reported in 45 publications up to May 20, 2021). The first review was published on April 30, 2020 [42] , the day after the first randomized trial of remdesivir and the preliminary findings of two other trials were published.…”
Section: Resultsmentioning
confidence: 99%
“…Nine were first published as preprints. Of these, three were subsequently published without any changes to the search date or studies included (shown as single reviews in Figure 1 ) [ 54 , 55 , 60 ], and one was updated with a new search and additional studies (shown as separate reviews in Figure 1 ) [ 49 , 50 ].
Figure 1 Timeline and currency of randomized trials and systematic reviews of remdesivir for COVID-19 [NB.
…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity across the studies may affect the study results ( 65 ). For instance, pooling the data of the original articles would be highly difficult due to heterogeneity in the study design and reported outcomes ( 25 ), and heterogeneity in disease severity could affect the treatment output.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that liver disturbance was rare in both groups, and that there was no statistical difference between the two groups. Thus, considering the duration of treatment and comparison with the placebo, we believe that the association between remdesivir and liver injury in patients with COVID-19 was weak (Roshanshad et al, 2020).…”
Section: Remdesivirmentioning
confidence: 98%